A spiral modified MBBR filler, a preparation method and application thereof
By designing a spiral-shaped modified MBBR packing material and using modified hydrotalcite, the problems of slow microbial biofilm formation, poor UV aging resistance, and insufficient hydraulic performance of MBBR packing material were solved, achieving efficient and low-energy wastewater treatment.
Patent Information
- Application Number
- CN202511437139.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-09
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-10-09
AI Technical Summary
Existing MBBR packing materials suffer from problems such as slow microbial biofilm formation, low biomass, poor resistance to UV aging, insufficient hydraulic performance, and high energy consumption, making them difficult to apply efficiently in complex industrial wastewater.
Spiral modified MBBR packing is used. HDPE is mixed with modified hydrotalcite, additives and other raw materials, extruded and granulated, and then sheared by a spiral cutter. The synergistic effect of modified hydrotalcite and additives enhances the hydrophilicity, UV aging resistance and hydraulic properties of the packing, and promotes microbial attachment and gas-liquid-solid three-phase mixing.
It improves the fluidization rate of the packing material, reduces energy consumption, enhances the pollutant degradation capacity, promotes the initial colonization of microorganisms and the stable formation of biofilm, and improves the removal efficiency of various pollutants.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of wastewater treatment technology, specifically to a spiral modified MBBR packing material, its preparation method, and its application. Background Technology
[0002] Moving bed biofilm reactors (MBBRs) are a highly efficient wastewater treatment technology. Their core lies in adding suspended carriers (MBBR packing material) to the reactor, significantly improving pollutant degradation efficiency by enhancing biomass and biodiversity within the system. In this process, microorganisms primarily grow on the surface of the packing material in the form of a biofilm. This not only avoids the limitations imposed by hydraulic retention time on the biological phase but also provides a stable living environment for long-sludge-age microorganisms (such as nitrifying bacteria), thereby strengthening the reactor's ability to simultaneously remove multiple pollutants. Therefore, the MBBR process outperforms the traditional activated sludge process in terms of treatment efficiency and operational stability.
[0003] MBBR packing, a key component of this process, is typically made from polyolefin materials (such as polyethylene and polypropylene) or polyurethane, and is produced through extrusion or injection molding. High-density polyethylene (HDPE) based packing is widely used in practical engineering due to its advantages such as high mechanical strength, low cost, ease of large-scale production, excellent fluidization performance, and high mass transfer efficiency. However, HDPE itself is a hydrophobic material with low surface energy and poor biocompatibility, resulting in slow initial attachment of microorganisms and insufficient biofilm formation capacity, leading to the problem of "slow biofilm initiation and low final biomass." Furthermore, HDPE packing is prone to aging under long-term UV exposure, leading to a decline in mechanical properties and functional stability, which in turn affects its long-term performance and pollutant degradation performance.
[0004] Traditional HDPE packing materials are mostly designed with simple cylindrical or ring structures. While easy to manufacture, their hydraulic performance has significant limitations. These structures have a single internal flow channel form, resulting in low specific surface area utilization. This easily leads to directional flow or short-circuiting within the reactor, causing uneven distribution of fluid shear force and low mixing efficiency. In fluidized states, the packing materials tend to exhibit regular translational motion, making it difficult to promote interphase mixing and mass transfer within the reactor. Some areas may even experience accumulation or dead zones, affecting biofilm renewal and substrate-biofilm contact efficiency. Furthermore, due to the limited interaction between the packing materials and the water flow, oxygen transfer efficiency and energy utilization are low. In actual operation, it is often necessary to increase the aeration intensity to achieve complete fluidization, resulting in increased energy consumption.
[0005] To improve the performance of filler materials, some studies have attempted to introduce functional additives, such as iron(III) oxide (Fe3O4), utilizing its magnetic and catalytic properties to enhance the degradation capacity of pollutants. However, as inorganic particles, Fe3O4 exhibits significant density differences and insufficient compatibility with the HDPE matrix. In actual operation, it is prone to peeling off from the surface due to collisions and friction between filler materials, resulting in loss of active ingredients and uneven fluidization. More importantly, under complex water quality conditions such as high chloride or high sulfate levels, Fe3O4 is susceptible to ion erosion and dissolution, leading to a rapid decline in its activity, which severely limits the application potential of this type of modified filler material in complex industrial wastewater.
[0006] Therefore, developing a modification strategy that can simultaneously improve the hydrophilicity, UV resistance, and pollutant degradation activity of MBBR packing materials, while also possessing excellent hydraulic properties, has become an important direction for enhancing MBBR process performance. By optimizing material formulations and designing a three-dimensional helical porous structure, the specific surface area of the packing material can be effectively increased, surface roughness enhanced, and a richer ecological niche provided for microbial attachment. Simultaneously, it promotes turbulence formation and gas-liquid-solid three-phase mixing, reducing fluidization energy consumption. This strategy of synergistic effect of functional components and structural modification holds promise for achieving efficient, stable, and low-energy-consumption biological wastewater treatment applications. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention provides a spiral modified MBBR packing, its preparation method, and its application.
[0008] The objective of this invention can be achieved through the following technical solutions: A spiral modified MBBR filler comprises the following raw materials in parts by weight: 100-105 parts HDPE, 7-9 parts modified hydrotalcite, 4-6 parts additives, 0.7-0.9 parts initiator, 1-2 parts polyvinyl alcohol, 1-2 parts chitosan, 1.5-3 parts gelatin, 5-10 parts activated carbon, 0.5-1 part zinc stearate, and 0.3-0.5 parts EBS dispersant; Furthermore, the initiator is dicumyl peroxide; The spiral-shaped modified MBBR packing is prepared by the following steps: HDPE and additives are heated and melted together, then an initiator is added. After the mixture is heated and melted, it is cooled down and modified hydrotalcite, polyvinyl alcohol, chitosan, gelatin, activated carbon, zinc stearate, and EBS dispersant are added and mixed. The mixture is then heated and melted together, extruded and granulated, and then thermoformed into cylindrical blanks by screw extrusion. The cylindrical blanks are then sheared with a carbide spiral cutter, soaked in water, dried, and then treated with plasma to obtain spiral modified MBBR filler. The preparation of the spiral modified MBBR packing includes the following specific steps: HDPE and additives are melt-mixed at 175-180℃, then an initiator is added, and the mixture is heated to 185-190℃ for 13-17 minutes. The mixture is then cooled to 80-90℃, and modified hydrotalcite, polyvinyl alcohol, chitosan, gelatin, activated carbon, zinc stearate, and EBS dispersant are added and mixed at 800-1000 rpm for 10-15 minutes. The mixture is then melt-blended at 190-200℃ and 300-400 rpm, extruded and granulated, and formed into cylindrical blanks using a screw extruder at 180-210℃. The cylindrical blanks are then sheared with a carbide spiral cutter, immersed in water at 75-80℃ for 1.8-2 hours, dried at 60-65℃ for 4-4.5 hours, and then treated with plasma to obtain spiral-shaped modified MBBR filler. Furthermore, the diameter of the cylindrical blank is 10-25mm, and the length-to-diameter ratio is 0.8-1.2; the helix angle of the carbide spiral cutter is 30-60°, the cutter width is 2-4mm, and the cutter depth is 1.5-3mm; during the shearing process of the carbide spiral cutter, the linear velocity is 0.5-1.5m / s, and the feed is 0.2-0.5mm / r; the plasma treatment conditions are a power of 300-500W and a time of 90-120s. Furthermore, the spiral-shaped modified MBBR packing is used for wastewater treatment; The modified hydrotalcite is prepared by the following steps: Step G1: Add thiophene aldehyde to acetic anhydride, stir, add potassium salt, heat and reflux with stirring to obtain product g1; add product g1 to DMF, stir and add thionyl chloride, heat and reflux with stirring to obtain product g2; mix nitroimidazole and DMSO, stir, and add the mixture of product g2 dropwise in an ice-water bath, heat and stir after the addition is complete to obtain product g3. Step G2: Mix product g3, DMAC, and ethanol solution, stir and add sodium dithionite, stir to obtain product g4; mix product g4, epichlorohydrin, and DMF, stir and add tetra-n-butylammonium chloride, heat and stir, then add alkaline solution, continue stirring to obtain product g5. Step G3: Add aldehyde pyrimidine to acetic anhydride, stir, add anhydrous potassium carbonate, heat and reflux and stir to obtain product g6; mix product g6, DMAC and triethylamine, stir, add product g5, heat and stir, then heat and stir again to obtain product g7. Step G4: Sodium carboxybenzenesulfonate, DMSO, and ethanol are mixed and stirred. Then, thionyl chloride is added, and the mixture is heated under reflux and stirred to obtain product g8. Product g7, ethyl acetate, and DMAC are mixed and stirred. Then, the mixture of product g8 is added to an ice-water bath and heated under reflux and stirred to obtain product g9. Under a protective gas atmosphere, product g9, DMF, and ethanol are mixed, and the mixture is refluxed and stirred. Then, aqueous acetic acid solution and zinc granules are added and refluxed and stirred to obtain product g10. Step G5: Add zinc chloride and aluminum chloride hexahydrate to deionized water, stir and adjust the pH, heat and stir, then age, wash and dry to obtain zinc aluminum hydrotalcite; add zinc aluminum hydrotalcite and product g10 to solvent 1, ultrasonically disperse, stir and adjust the pH, heat and stir, wash until neutral and dry to obtain modified hydrotalcite. The preparation of the modified hydrotalcite includes the following specific steps: Step G1: Add thiophene aldehyde to acetic anhydride, stir for 5-10 min, add potassium salt and turn on reflux, heat to 95-105℃, stir for 2.5-3 h to obtain product g1; add product g1 to DMF, stir and add thionyl chloride, heat to 55-60℃, reflux and stir for 4-4.5 h to obtain product g2; mix nitroimidazole and DMSO, stir for 20-25 min, add the mixture of product g2 dropwise in an ice-water bath, heat to 50-55℃ after the addition is complete, stir and react for 7.5-8 h to obtain product g3; Further, the ratio of thiophene aldehyde, acetic anhydride, and potassium salt is 5.8-6.2g: 5-5.4g: 1.4-2.0g; the thiophene aldehyde is 3-thiophenecaraldehyde; the potassium salt is anhydrous potassium carbonate; the ratio of product g1, DMF, and thionyl chloride is 6.5-7g: 30-35mL: 6-6.5g; the ratio of the mixture of nitroimidazole, DMSO, and product g2 is 5.9-6.3g: 13-15mL: 25-30mL; the nitroimidazole is 4-nitroimidazole; the mixture of product g2 is obtained by mixing product g2 and DMSO at a ratio of 7.5-8g: 15-20mL. In step G1, the aldehyde group of thiophene aldehyde reacts with acetic anhydride to give thiophene containing an alkenoic acid; the carboxyl group of product g1 reacts with thionyl chloride to give product g2 containing an acyl chloride; the acyl chloride of product g2 reacts with the secondary amine of product g2 to give product g3. Step G2: Mix product g3, DMAC, and ethanol solution, stir for 30-35 min, add sodium dithionite, and stir the reaction at pH 8-8.5 and 45-50℃ for 2.8-3.2 h to obtain product g4; mix product g4, epichlorohydrin, and DMF, stir for 30-40 min, add tetra-n-butylammonium chloride, and stir the reaction at 95-100℃ for 2-3 h, then add alkaline solution and continue stirring for 1.5-2 h to obtain product g5; Further, the ratio of product g3, DMAC, ethanol solution, and sodium dithionite is 13.5-14.5g: 28-32mL: 25-30mL: 8.5-9g; the ethanol solution is obtained by mixing 95% ethanol and water in a volume ratio of 2-2.5: 1-1.5; the ratio of product g4, epichlorohydrin, DMF, tetrabutylammonium chloride, and alkaline solution is 12-12.5g: 9.6-10.0g: 45-55mL: 40-50mg: 20-24mL; the alkaline solution is a 40-45% potassium hydroxide or sodium hydroxide solution. During step G2, the nitro group of product g3 is reduced to an amino group to obtain product g4; the amino group of product g4 reacts with epichlorohydrin to first open the ring and then close the ring to obtain product g5 with an epoxy group. Step G3: Add aldehyde pyrimidine to acetic anhydride, stir for 20-25 min, add anhydrous potassium carbonate and turn on reflux, heat to 90-100℃, stir for 3.5-4 h to obtain product g6; mix product g6, DMAC and triethylamine, stir for 35-40 min, add product g5, heat to 75-85℃, stir for 7.5-8 h, heat to 105-110℃, continue stirring for 1.5-1.7 h to obtain product g7; Furthermore, the ratio of aldehyde pyrimidine, acetic anhydride, and anhydrous potassium carbonate is 7.0-7.5g: 5.5-6g: 1.8-2.2g; the aldehyde pyrimidine is 2-methoxy-5-aldehyde pyrimidine; the ratio of product g6, DMAC, triethylamine, and product g5 is 7.8-8.2g: 65-70mL: 0.2-0.3g: 22.5-23g. In step G3, the aldehyde group of the aldehyde pyrimidine reacts with acetic anhydride to give a pyrimidine containing an olefinic acid, i.e., product g6; the carboxyl group of product g6 reacts with the epoxy group of product g5 in a ring-opening reaction to give product g7 containing a secondary alcohol hydroxyl group. Step G4: Sodium carboxybenzenesulfonate, DMSO, and ethanol are mixed and stirred at 35-40℃ for 30-40 min. Thionyl chloride is added, and the mixture is refluxed and stirred at 60-65℃ for 2.5-3 h to obtain product g8. Product g7, ethyl acetate, and DMAC are mixed and stirred for 40-45 min. The mixture of product g8 is added to an ice-water bath, and the mixture is heated to 70-80℃ and refluxed and stirred for 10-10.5 h to obtain product g9. Under a protective gas atmosphere, product g9, DMF, and ethanol are mixed and refluxed and stirred for 30-35 min. An aqueous solution of acetic acid and zinc granules are added, and the mixture is refluxed and stirred at 85-90℃ for 2-2.5 h to obtain product g10. Further, the ratio of sodium carboxybenzenesulfonate, DMSO, ethanol, and thionyl chloride is 11.5-12g:25-30mL:15-20mL:7.5-8g; the sodium carboxybenzenesulfonate is 3-carboxybenzenesulfonate; the volume fraction of ethanol is 95%; the ratio of the mixture of product g7, ethyl acetate, DMAC, and product g8 is 30-31g:20-25mL:40-45mL:45-50mL; the mixture of product g8 is obtained by mixing product g8 and DMF at a ratio of 13.5-14g:30-35mL; the ratio of product g9, DMF, ethanol, aqueous acetic acid solution, and zinc granules is 45-46g:55-65mL:35-45mL:18-22mL:3.5-4g; the concentration of the aqueous acetic acid solution is 1.8-2.0mol / L; the volume fraction of ethanol is 95%. In step G4, the carboxyl group of sodium carboxybenzenesulfonate is converted into an acyl chloride to obtain product g8; the acyl chloride of product g8 reacts with the secondary alcohol hydroxyl group of product g7 to obtain product g9; the phenol methyl ether of product g9 is converted into a phenolic hydroxyl group to obtain product g10. Step G5: Add zinc chloride and aluminum chloride hexahydrate to deionized water, stir for 5-10 min, adjust the pH to 9-10 with 10-15% sodium hydroxide solution, stir and react at 70-80℃ for 2-2.5 h, then age for 12-13 h, wash until neutral, and dry at 80-85℃ for 7-7.5 h to obtain zinc-aluminum hydrotalcite; add zinc-aluminum hydrotalcite and product g10 to solvent 1, ultrasonically disperse for 20-30 min, stir and adjust the pH to 5.5-6, stir and react at 80-85℃ for 4-4.5 h, wash until neutral, and dry at 70-75℃ to obtain modified hydrotalcite; Furthermore, the ratio of zinc chloride, aluminum chloride hexahydrate, and deionized water is 0.2-0.25 mol : 0.1-0.14 mol : 80-85 mL; the ratio of zinc aluminum hydrotalcite, product g10, and solvent 1 is 6.5-7.5 g : 1.3-1.5 g : 30-40 mL; solvent 1 is obtained by mixing ethanol and water in a volume ratio of 2-2.5:1; the volume fraction of ethanol is 95%. In step G5, zinc-aluminum hydrotalcite was prepared by coprecipitation, and then the zinc-aluminum hydrotalcite was modified by intercalation with sodium sulfonate of product g10 to obtain modified hydrotalcite. The preparation of the auxiliary agent includes the following steps: Step H1: Add nano-iron oxide to anhydrous ethanol, disperse by ultrasonication, add hydrogen peroxide solution, heat and stir to obtain pretreated product; add pretreated product to ethanol, disperse by ultrasonication, add silane hydrolysate, heat and stir to obtain product h1; Step H2: Mix carbon nanotubes and acid solution, heat and reflux with stirring to obtain product h2; mix product h1, anhydrous ethanol, DMF and triethylamine, stir and then add product h2, heat and stir to obtain product h3. Step H3: Triphenylphosphine, bromoethanol, and anhydrous acetonitrile are mixed, a protective gas is introduced, and the mixture is heated and stirred to obtain product h4; product h4, epichlorohydrin, methanol, and DMSO are mixed, and an aqueous sodium hydroxide solution is added while stirring, and the mixture is heated and stirred to obtain product h5; Step H4: Mix product h3, acetonitrile, and methanol and disperse by ultrasonication. Add N,N-dimethylbutylamine and product h5, and heat and reflux to obtain product h6. Mix product h6, potassium carbonate, DMSO, and acetonitrile and disperse by ultrasonication. Add acryloyl chloride mixture in an ice-water bath, and heat and stir after addition to obtain the additive. The preparation of the auxiliary agent includes the following specific steps: Step H1: Add nano-iron oxide to anhydrous ethanol, sonicate for 30-35 min, add hydrogen peroxide solution dropwise, heat to 45-50℃, stir for 1-1.2 h to obtain the pretreated product; add the pretreated product to ethanol, sonicate for 25-30 min, add silane hydrolysis solution, stir at 60-65℃ for 4-4.5 h to obtain product h1; Further, the ratio of nano-ferric oxide, anhydrous ethanol, and hydrogen peroxide solution is 1-2 g: 35-45 mL: 30-40 mL; the mass fraction of hydrogen peroxide solution is 5-10%; the ratio of pretreated product, ethanol, and silane hydrolysate is 1.5-2.5 g: 40-45 mL: 25-30 mL; the silane hydrolysate is obtained by mixing and stirring silane and solvent a, adjusting the pH to 5-5.5, and then stirring at room temperature for 1.5-2 h; the silane is 5,6-epoxyhexyltriethoxysilane; the volume fraction of ethanol is 95%; the ratio of silane to solvent a in the silane hydrolysate is 14-14.5 g: 30-32 mL; solvent a is obtained by mixing ethanol and water in a volume ratio of 1-1.5:1. In step H1, after being treated with hydrogen peroxide solution, the surface of nano-iron oxide has increased oxygen-containing functional groups such as hydroxyl groups, resulting in a pretreated product. The pretreated product is then treated with silane hydrolysis solution to obtain nano-iron oxide with epoxy groups on the surface, i.e., product h1. Step H2: Mix carbon nanotubes and acid solution, heat to 80-85℃, reflux and stir for 1-1.2h to obtain product h2; mix product h1, anhydrous ethanol, DMF and triethylamine, stir for 35-40min, add product h2, stir at 80-90℃ for 10-10.5h, raise the temperature to 100-110℃, and continue stirring for 2-2.2h to obtain product h3; Furthermore, the ratio of carbon nanotubes to acid solution is 1-1.5g:30-40mL; the acid solution is a mixture of 68% concentrated nitric acid and 98% concentrated sulfuric acid in a volume ratio of 1-3:2-3; the ratio of product h1, anhydrous ethanol, DMF, triethylamine, and product h2 is 2-2.5g:25-35mL:90-100mL:1-1.2g:3-4g. In step H2, carbon nanotubes are treated with acid to obtain surface carboxylated carbon nanotubes, i.e., product h2; the carboxyl groups of product h2 react with the epoxy groups of product h1 to obtain a grafted product of carbon nanotubes containing secondary alcohol hydroxyl groups and nano-iron oxide, i.e., product h3. Step H3: Triphenylphosphine, bromoethanol, and anhydrous acetonitrile are mixed, a protective gas is introduced, and the mixture is heated to 40-45°C with stirring for 24-24.5 h to obtain product h4; product h4, epichlorohydrin, methanol, and DMSO are mixed, and an aqueous sodium hydroxide solution is added with stirring, and the mixture is heated to 55-60°C with stirring for 4.5-5 h to obtain product h5; Furthermore, the ratio of triphenylphosphine, bromoethanol, and anhydrous acetonitrile is 14-14.5g:9-9.5g:60-70mL; the bromoethanol is 5-bromo-1-pentanol; the ratio of product h4, epichlorohydrin, methanol, DMSO, and sodium hydroxide aqueous solution is 24-25g:5-5.5g:15-20mL:50-55mL:30-35mL; the mass fraction of the sodium hydroxide aqueous solution is 20-25%. In step H3, triphenylphosphine reacts with bromoalcohol via a nucleophilic substitution reaction to generate a quaternary phosphonium salt containing a primary alcohol, i.e., product h4; the primary alcohol hydroxyl group of product h4 undergoes ring opening and ring closing with epichlorohydrin to give product h5 containing an epoxy group. Step H4: Mix product h3, acetonitrile, and methanol and ultrasonically disperse for 40-50 min. Add N,N-dimethylbutylamine and product h5, and reflux and stir at 90-100℃ for 6-6.5 h to obtain product h6. Mix product h6, potassium carbonate, DMSO, and acetonitrile and ultrasonically disperse for 1-1.2 h. Add acryloyl chloride mixture in an ice-water bath. After the addition is complete, raise the temperature to 50-55℃ and stir for 12-12.5 h to obtain the auxiliary agent. Furthermore, the ratio of product h3, acetonitrile, methanol, N,N-dimethylbutylamine, and product h5 is 7-8g:150-160mL:20-30mL:0.7-0.9g:15-16g; the ratio of product h6, potassium carbonate, DMSO, acetonitrile, and acryloyl chloride mixture is 25-26g:2-2.5g:170-180mL:35-45mL:35-40mL; the acryloyl chloride mixture is obtained by mixing acryloyl chloride and DMSO at a ratio of 4.6-5g:15-20mL. In step H4, the secondary alcohol of product h3 reacts with the epoxy group of product h5 to obtain product h6 containing hydroxyl groups; acryloyl chloride reacts with the hydroxyl group of product h6 to obtain an auxiliary agent containing terminal carbon-carbon double bonds. The beneficial effects of this invention are as follows: This invention discloses a spiral modified MBBR packing, its preparation method, and its application. The spiral modified MBBR packing is obtained by mixing and extruding raw materials such as HDPE, modified hydrotalcite, and additives, followed by screw extrusion thermoforming into a cylindrical blank, and then cutting it with a spiral cutter. The spiral modified MBBR packing has a high fluidization rate, which helps to reduce energy consumption.
[0009] The modified hydrotalcite is obtained by intercalating zinc-aluminum hydrotalcite with products obtained from the reaction of thiophene formaldehyde, nitroimidazole, aldehyde pyrimidine, and sodium carboxybenzenesulfonate. The combination of thiophene formaldehyde, nitroimidazole, and aldehyde pyrimidine forms a conjugated system containing thiophene and nitrogen-containing heterocycles with a strong conjugation effect. This broadens the UV absorption range, overcomes the limitation of thiophene's small UV absorption range, enhances UV absorption and converts it into other forms of energy. Furthermore, the hydroxyl groups formed on the pyrimidine ring have free radical scavenging capabilities, which can terminate chain reactions and provide strong anti-aging properties. When combined with the products obtained from the reaction of sodium carboxybenzenesulfonate, the positive charge on the surface of the zinc-aluminum hydrotalcite helps the modified hydrotalcite attract negatively charged microorganisms through the attraction of positive and negative charges, enhancing the adsorption and fixation between the filler and microorganisms, thereby increasing the biofilm formation rate. The physical UV-blocking ability of the zinc-aluminum hydrotalcite, combined with the conjugated system and the hydroxyl groups on the pyrimidine ring, prevents UV damage to the filler, further endowing it with strong anti-aging properties and extending its service life.
[0010] The additive is a product obtained by reacting silane-modified nano-ferric oxide, carboxylated carbon nanotubes, triphenylphosphine, bromool, acryloyl chloride, etc.; by combining silane-modified nano-ferric oxide and carboxylated carbon nanotubes, the carbon nanotubes reduce the contact probability between chloride ions, sulfate ions and other salts and iron active sites through physical isolation. By utilizing the magnetic properties of ferric oxide and the conductivity of carbon nanotubes, a heterojunction interface is formed, which accelerates electron transfer, enhances catalytic activity, and compensates for the deficiency of catalytic activity caused by the accelerated dissolution of ferric oxide by chloride ions, sulfate ions and other salts. Furthermore, by combining the use of triphenylphosphine and bromoethanol, quaternary phosphonium salts are formed in the additives. After the additives are melt-grafted with HDPE, the hydrophilicity of the HDPE surface is enhanced, reducing the difficulty for microorganisms to initially attach to the filler. After the additives are melt-grafted with HDPE, the compatibility of nano-ferric oxide, carbon nanotubes, and hydroxyl-modified hydrotalcite with the matrix is greatly improved, which helps to form a uniform whole and avoids uneven fluidization of the filler caused by the large density difference between nano-ferric oxide and HDPE. At the same time, it avoids the detachment of ferric oxide particles due to excessive friction, thus improving the stability of the biofilm.
[0011] This invention, through its three-dimensional helical structure design, firstly significantly improves the hydraulic performance of the packing material. Its unique three-dimensional morphology effectively disrupts steady-state water flow, promotes turbulence within the reactor, enhances gas-liquid-solid three-phase mixing efficiency, avoids short-circuiting and packing material accumulation, significantly improves mass transfer and oxygen utilization, and achieves good fluidization even at lower aeration intensities, effectively reducing system operating energy consumption. Secondly, the helical structure significantly increases the specific surface area of the packing material and provides diverse spatial niches for microbial attachment. Combined with a modified, highly biocompatible surface, it further facilitates initial microbial colonization and stable biofilm formation, accelerating the biofilm initiation process, increasing the total biofilm volume and population diversity, thereby enhancing the simultaneous removal capacity of multiple pollutants such as COD, TN, and TP. Attached Figure Description
[0012] Figure 1 This is a side view of the spiral modified MBBR packing (28) of Embodiments 7-9 of the present invention; the sidewall of the spiral modified MBBR packing (28) is formed as a three-dimensional spiral flow channel (281).
[0013] Figure 2 This is a top view of the spiral modified MBBR packing (28) of Examples 7-9 of the present invention. Detailed Implementation
[0014] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0015] Example 1 A modified hydrotalcite, the preparation of which includes the following specific steps: Step G1: Add 3-thiophenecaraldehyde to acetic anhydride, stir for 5 min, add anhydrous potassium carbonate, turn on reflux, heat to 95°C, stir for 2.5 h to obtain product g1; add product g1 to DMF, stir and add thionyl chloride, heat to 55°C, reflux and stir for 4 h to obtain product g2; mix 4-nitroimidazole and DMSO, stir for 20 min, add the mixture of product g2 dropwise in an ice-water bath, heat to 50°C, and stir the reaction. After 7.5 h, product g3 was obtained; the ratio of 3-thiophenecarboxaldehyde, acetic anhydride, and anhydrous potassium carbonate was 5.8 g: 5 g: 1.4 g; the ratio of product g1, DMF, and thionyl chloride was 6.5 g: 30 mL: 6 g; the ratio of the mixture of 4-nitroimidazole, DMSO, and product g2 was 5.9 g: 13 mL: 25 mL; the mixture of product g2 was obtained by mixing product g2 and DMSO at a ratio of 7.5 g: 15 mL. Step G2: Mix product g3, DMAC, and ethanol solution, stir for 30 min, add sodium dithionite, and stir for 2.8 h at pH 8.1 and 45℃ to obtain product g4; mix product g4, epichlorohydrin, and DMF, stir for 30 min, add tetra-n-butylammonium chloride, and stir for 2 h at 95℃, then add alkaline solution and continue stirring for 1.5 h to obtain product g5; the ratio of product g3, DMAC, ethanol solution, and sodium dithionite is 13.5 g: 28 mL: 25 mL: 8.5 g; the ethanol solution is obtained by mixing 95% ethanol and water in a 2:1 volume ratio; the ratio of product g4, epichlorohydrin, DMF, tetra-n-butylammonium chloride, and alkaline solution is 12 g: 9.6 g: 45 mL: 40 mg: 20 mL; the alkaline solution is a 40% potassium hydroxide or sodium hydroxide solution. Step G3: Add 2-methoxy-5-aldehyde pyrimidine to acetic anhydride, stir for 20 min, add anhydrous potassium carbonate, turn on reflux, heat to 90℃, stir for 3.5 h to obtain product g6; mix product g6, DMAC, and triethylamine, stir for 35 min, add product g5, heat to 75℃, stir for 7.5 h, heat to 105℃, continue stirring for 1.5 h to obtain product g7; the ratio of 2-methoxy-5-aldehyde pyrimidine, acetic anhydride, and anhydrous potassium carbonate is 7.0 g: 5 g: 1.8 g; the ratio of product g6, DMAC, triethylamine, and product g5 is 7.8 g: 65 mL: 0.2 g: 22.5 g. Step G4: Sodium 3-carboxybenzenesulfonate, DMSO, and ethanol are mixed and stirred at 35°C for 30 min. Thionyl chloride is added, and the mixture is refluxed and stirred at 60°C for 2.5 h to obtain product g8. Product g7, ethyl acetate, and DMAC are mixed and stirred for 40 min. The mixture of product g8 is added to an ice-water bath, and the mixture is heated to 70°C and refluxed and stirred for 10 h to obtain product g9. Under a nitrogen atmosphere, product g9, DMF, and ethanol are mixed and refluxed and stirred for 30 min. An aqueous solution of acetic acid and zinc granules are added, and the mixture is refluxed and stirred at 85°C for 2 h to obtain product g10. Sodium 3-carboxybenzenesulfonate and DMS The ratio of O, ethanol, and thionyl chloride is 11.5g:25mL:15mL:7.5g; the volume fraction of ethanol is 95%. The ratio of the mixture of product g7, ethyl acetate, DMAC, and product g8 is 30g:20mL:40mL:45mL; the mixture of product g8 is obtained by mixing product g8 and DMF in a ratio of 13.5g:30mL. The ratio of product g9, DMF, ethanol, aqueous acetic acid solution, and zinc granules is 45g:55mL:35mL:18mL:3.5g; the concentration of the aqueous acetic acid solution is 1.8mol / L; the volume fraction of ethanol is 95%. Step G5: Add zinc chloride and aluminum chloride hexahydrate to deionized water, stir for 5 min, adjust the pH to 9 with 10% sodium hydroxide solution, stir and react at 70℃ for 2 h, then age for 12 h, wash until neutral, and dry at 80℃ for 7 h to obtain zinc-aluminum hydrotalcite; add zinc-aluminum hydrotalcite and product g10 to solvent 1, ultrasonically disperse for 20 min, stir and adjust the pH to 5.5, stir and react at 80℃ for 4 h, wash until neutral, and dry at 70℃ to obtain modified hydrotalcite; the volume ratio of zinc chloride, aluminum chloride hexahydrate, and deionized water is 0.2 mol: 0.1 mol: 80 mL; the volume ratio of zinc-aluminum hydrotalcite, product g10, and solvent 1 is 6.5 g: 1.3 g: 30 mL; solvent 1 is a mixture of ethanol and water in a 2:1 volume ratio; the volume fraction of ethanol is 95%.
[0016] Example 2 A modified hydrotalcite, the preparation of which includes the following specific steps: Step G1: Add 3-thiophenecarboxaldehyde to acetic anhydride, stir for 8 min, add anhydrous potassium carbonate, turn on reflux, heat to 100℃, stir for 2.8 h to obtain product g1; add product g1 to DMF, stir, add thionyl chloride, heat to 58℃, reflux and stir for 4.3 h to obtain product g2; mix 4-nitroimidazole and DMSO, stir for 23 min, add the mixture of product g2 dropwise in an ice-water bath, heat to 53℃ after the addition is complete, and stir the reaction. After 7.8 h, product g3 was obtained; the ratio of 3-thiophenecarboxaldehyde, acetic anhydride, and anhydrous potassium carbonate was 6.0 g: 5.2 g: 1.7 g; the ratio of product g1, DMF, and thionyl chloride was 6.8 g: 33 mL: 6.3 g; the ratio of the mixture of 4-nitroimidazole, DMSO, and product g2 was 6.1 g: 14 mL: 28 mL; the mixture of product g2 was obtained by mixing product g2 and DMSO at a ratio of 7.8 g: 17 mL. Step G2: Mix product g3, DMAC, and ethanol solution, stir for 33 min, add sodium dithionite, and stir at pH 8.2 and 48℃ for 3.0 h to obtain product g4; mix product g4, epichlorohydrin, and DMF, stir for 35 min, add tetra-n-butylammonium chloride, and stir at 98℃ for 2.5 h, then add alkaline solution and continue stirring for 1.8 h to obtain product g5; the ratio of product g3, DMAC, ethanol solution, and sodium dithionite is 14.0 g: 30 mL: 28 mL: 8.8 g; the ethanol solution is obtained by mixing 95% ethanol and water in a volume ratio of 2.3: 1.3; the ratio of product g4, epichlorohydrin, DMF, tetra-n-butylammonium chloride, and alkaline solution is 12.3 g: 9.8 g: 50 mL: 45 mg: 22 mL; the alkaline solution is a 43% potassium hydroxide or sodium hydroxide solution. Step G3: Add 2-methoxy-5-aldehyde pyrimidine to acetic anhydride, stir for 23 min, add anhydrous potassium carbonate, turn on reflux, heat to 95℃, stir for 3.8 h to obtain product g6; mix product g6, DMAC, and triethylamine, stir for 38 min, add product g5, heat to 80℃, stir for 7.8 h, heat to 107℃, continue stirring for 1.6 h to obtain product g7; the ratio of 2-methoxy-5-aldehyde pyrimidine, acetic anhydride, and anhydrous potassium carbonate is 7.3 g: 5.8 g: 2.0 g; the ratio of product g6, DMAC, triethylamine, and product g5 is 8.0 g: 68 mL: 0.25 g: 22.8 g. Step G4: Sodium 3-carboxybenzenesulfonate, DMSO, and ethanol were mixed and stirred at 38°C for 35 min. Thionyl chloride was added, and the mixture was refluxed and stirred at 63°C for 2.8 h to obtain product g8. Product g7, ethyl acetate, and DMAC were mixed and stirred for 43 min. The mixture of product g8 was added to an ice-water bath, and the mixture was heated to 75°C and refluxed and stirred for 10.3 h to obtain product g9. Under a nitrogen atmosphere, product g9, DMF, and ethanol were mixed and refluxed and stirred for 33 min. An aqueous solution of acetic acid and zinc granules were added, and the mixture was refluxed and stirred at 88°C for 2.3 h to obtain product g10. Sodium 3-carboxybenzenesulfonate and DMS The ratio of O, ethanol, and thionyl chloride is 11.8 g: 28 mL: 18 mL: 7.8 g; the volume fraction of ethanol is 95%. The ratio of the mixture of product g7, ethyl acetate, DMAC, and product g8 is 30.5 g: 23 mL: 43 mL: 48 mL; the mixture of product g8 is obtained by mixing product g8 and DMF in a ratio of 13.8 g: 33 mL. The ratio of product g9, DMF, ethanol, aqueous acetic acid solution, and zinc granules is 45.5 g: 60 mL: 40 mL: 20 mL: 3.8 g; the concentration of the aqueous acetic acid solution is 1.9 mol / L; the volume fraction of ethanol is 95%. Step G5: Add zinc chloride and aluminum chloride hexahydrate to deionized water, stir for 8 min, adjust the pH to 9.5 with 13% sodium hydroxide solution, stir and react at 75℃ for 2.3 h, then age for 12.5 h, wash until neutral, and dry at 83℃ for 7.3 h to obtain zinc-aluminum hydrotalcite; add zinc-aluminum hydrotalcite and product g10 to solvent 1, ultrasonically disperse for 25 min, stir and adjust the pH to 5.8, stir and react at 83℃ for 4.3 h, wash until neutral, and dry at 73℃ to obtain modified hydrotalcite; the volume ratio of zinc chloride, aluminum chloride hexahydrate, and deionized water is 0.23 mol: 0.12 mol: 83 mL; the volume ratio of zinc-aluminum hydrotalcite, product g10, and solvent 1 is 7.0 g: 1.4 g: 35 mL; solvent 1 is a mixture of ethanol and water in a volume ratio of 2.3:1; the volume fraction of ethanol is 95%.
[0017] Example 3 A modified hydrotalcite, the preparation of which includes the following specific steps: Step G1: Add 3-thiophenecaraldehyde to acetic anhydride, stir for 10 min, add anhydrous potassium carbonate, turn on reflux, heat to 105℃, stir for 3 h to obtain product g1; add product g1 to DMF, stir, add thionyl chloride, heat to 60℃, reflux and stir for 4.5 h to obtain product g2; mix 4-nitroimidazole and DMSO, stir for 25 min, add the mixture of product g2 dropwise in an ice-water bath, heat to 55℃ after the addition is complete, and stir. The reaction was carried out for 8 hours to obtain product g3; the ratio of 3-thiophenecarboxaldehyde, acetic anhydride, and anhydrous potassium carbonate was 6.2 g: 5.4 g: 2.0 g; the ratio of product g1, DMF, and thionyl chloride was 7 g: 35 mL: 6.5 g; the ratio of the mixture of 4-nitroimidazole, DMSO, and product g2 was 6.3 g: 15 mL: 30 mL; the mixture of product g2 was obtained by mixing product g2 and DMSO at a ratio of 8 g: 20 mL. Step G2: Mix product g3, DMAC, and ethanol solution, stir for 35 min, add sodium dithionite, and stir at pH 8.5 and 50℃ for 3.2 h to obtain product g4; mix product g4, epichlorohydrin, and DMF, stir for 40 min, add tetra-n-butylammonium chloride, stir at 100℃ for 3 h, then add alkaline solution and continue stirring for 2 h to obtain product g5; the ratio of product g3, DMAC, ethanol solution, and sodium dithionite is 14.5 g: 32 mL: 30 mL: 9 g; the ethanol solution is obtained by mixing 95% ethanol and water in a volume ratio of 2.5: 1.5; the ratio of product g4, epichlorohydrin, DMF, tetra-n-butylammonium chloride, and alkaline solution is 12.5 g: 10.0 g: 55 mL: 50 mg: 24 mL; the alkaline solution is a 45% potassium hydroxide or sodium hydroxide solution. Step G3: Add 2-methoxy-5-aldehyde pyrimidine to acetic anhydride, stir for 25 min, add anhydrous potassium carbonate, turn on reflux, heat to 100℃, stir for 4 h to obtain product g6; mix product g6, DMAC, and triethylamine, stir for 40 min, add product g5, heat to 85℃, stir for 8 h, heat to 110℃, continue stirring for 1.7 h to obtain product g7; the ratio of 2-methoxy-5-aldehyde pyrimidine, acetic anhydride, and anhydrous potassium carbonate is 7.5 g: 6 g: 2.2 g; the ratio of product g6, DMAC, triethylamine, and product g5 is 8.2 g: 70 mL: 0.3 g: 23 g; Step G4: Sodium 3-carboxybenzenesulfonate, DMSO, and ethanol were mixed and stirred at 40°C for 40 min. Thionyl chloride was added, and the mixture was refluxed and stirred at 65°C for 3 h to obtain product g8. Product g7, ethyl acetate, and DMAC were mixed and stirred for 45 min. The mixture of product g8 was added to an ice-water bath, and the mixture was heated to 80°C and refluxed and stirred for 10.5 h to obtain product g9. Under a nitrogen atmosphere, product g9, DMF, and ethanol were mixed and refluxed and stirred for 35 min. An aqueous solution of acetic acid and zinc granules were added, and the mixture was refluxed and stirred at 90°C for 2.5 h to obtain product g10. 3-Carboxybenzenesulfonic acid The ratio of sodium, DMSO, ethanol, and thionyl chloride was 12g:30mL:20mL:8g; the volume fraction of ethanol was 95%. The ratio of the mixture of product g7, ethyl acetate, DMAC, and product g8 was 31g:25mL:45mL:50mL; the mixture of product g8 was obtained by mixing product g8 and DMF in a ratio of 14g:35mL. The ratio of product g9, DMF, ethanol, aqueous acetic acid solution, and zinc granules was 46g:65mL:45mL:22mL:4g; the concentration of the aqueous acetic acid solution was 2.0mol / L; the volume fraction of ethanol was 95%. Step G5: Add zinc chloride and aluminum chloride hexahydrate to deionized water, stir for 10 min, adjust the pH to 10 with 15% sodium hydroxide solution, stir and react at 80℃ for 2.5 h, then age for 13 h, wash until neutral, and dry at 85℃ for 7.5 h to obtain zinc-aluminum hydrotalcite; add zinc-aluminum hydrotalcite and product g10 to solvent 1, ultrasonically disperse for 30 min, stir and adjust the pH to 6, stir and react at 85℃ for 4.5 h, wash until neutral, and dry at 75℃ to obtain modified hydrotalcite; the volume ratio of zinc chloride, aluminum chloride hexahydrate, and deionized water is 0.25 mol: 0.14 mol: 85 mL; the volume ratio of zinc-aluminum hydrotalcite, product g10, and solvent 1 is 7.5 g: 1.5 g: 40 mL; solvent 1 is a mixture of ethanol and water in a volume ratio of 2.5:1; the volume fraction of ethanol is 95%.
[0018] Example 4 An auxiliary agent, the preparation of which includes the following steps: Step H1: Nano-ferric oxide was added to anhydrous ethanol and ultrasonically dispersed for 30 min. Hydrogen peroxide solution was added dropwise, and the mixture was heated to 45°C and stirred for 1 h to obtain the pretreated product. The pretreated product was then added to ethanol and ultrasonically dispersed for 25 min. Silane hydrolysis solution was added, and the mixture was stirred at 60°C for 4 h to obtain product h1. The ratio of nano-ferric oxide, anhydrous ethanol, and hydrogen peroxide solution was 1 g:35 mL:30 mL; the mass fraction of the hydrogen peroxide solution was 5%. The ratio of pretreated product, ethanol, and silane hydrolysate was 1.5 g: 40 mL: 25 mL. The silane hydrolysate was obtained by mixing and stirring 5,6-epoxyhexyltriethoxysilane and solvent a, adjusting the pH to 5.1, and then stirring at room temperature for 1.5 h. The ratio of 5,6-epoxyhexyltriethoxysilane to solvent a in the silane hydrolysate was 14 g: 30 mL. Solvent a was obtained by mixing ethanol and water in a volume ratio of 1:1. The volume fraction of ethanol was 95%. Step H2: Mix carbon nanotubes and acid solution, heat to 80℃, and reflux and stir for 1 hour to obtain product h2; mix product h1, anhydrous ethanol, DMF, and triethylamine, stir for 35 minutes, add product h2, stir at 80℃ for 10 hours, raise the temperature to 100℃, and continue stirring for 2 hours to obtain product h3; the volume ratio of carbon nanotubes to acid solution is 1g:30mL; the acid solution is obtained by mixing 68% concentrated nitric acid and 98% concentrated sulfuric acid in a volume ratio of 1:2; the volume ratio of product h1, anhydrous ethanol, DMF, triethylamine, and product h2 is 2g:25mL:90mL:1g:3g; Step H3: Triphenylphosphine, 5-bromo-1-pentanol, and anhydrous acetonitrile were mixed, nitrogen gas was introduced, and the mixture was heated to 40°C with stirring for 24 hours to obtain product h4. Product h4, epichlorohydrin, methanol, and DMSO were mixed, and sodium hydroxide aqueous solution was added with stirring. The mixture was heated to 55°C and stirred for 4.5 hours to obtain product h5. The molar ratio of triphenylphosphine, 5-bromo-1-pentanol, and anhydrous acetonitrile was 14 g: 9 g: 60 mL; the molar ratio of product h4, epichlorohydrin, methanol, DMSO, and sodium hydroxide aqueous solution was 24 g: 5 g: 15 mL: 50 mL: 30 mL; the mass fraction of the sodium hydroxide aqueous solution was 20%. Step H4: Mix product h3, acetonitrile, and methanol and ultrasonically disperse for 40 min. Add N,N-dimethylbutylamine and product h5, and reflux and stir at 90℃ for 6 h to obtain product h6. Mix product h6, potassium carbonate, DMSO, and acetonitrile and ultrasonically disperse for 1 h. Add acryloyl chloride mixture in an ice-water bath. After addition, raise the temperature to 50℃ and stir for 12 h to obtain the auxiliary agent. The ratio of product h3, acetonitrile, methanol, N,N-dimethylbutylamine, and product h5 is 7 g: 150 mL: 20 mL: 0.7 g: 15 g. The ratio of product h6, potassium carbonate, DMSO, acetonitrile, and acryloyl chloride mixture is 25 g: 2 g: 170 mL: 35 mL: 35 mL. The acryloyl chloride mixture is obtained by mixing acryloyl chloride and DMSO at a ratio of 4.6 g: 15 mL.
[0019] Example 5 An auxiliary agent, the preparation of which includes the following steps: Step H1: Nano-ferric oxide was added to anhydrous ethanol and ultrasonically dispersed for 33 min. Hydrogen peroxide solution was added dropwise, and the mixture was heated to 48°C and stirred for 1.1 h to obtain the pretreated product. The pretreated product was then added to ethanol and ultrasonically dispersed for 28 min. Silane hydrolysis solution was added, and the mixture was stirred at 63°C for 4.3 h to obtain product h1. The ratio of nano-ferric oxide, anhydrous ethanol, and hydrogen peroxide solution was 1.5 g: 40 mL: 35 mL; the mass fraction of the hydrogen peroxide solution was 8%. The percentage of pretreated product, ethanol, and silane hydrolysate was 2.0 g: 43 mL: 28 mL. The silane hydrolysate was obtained by mixing and stirring 5,6-epoxyhexyltriethoxysilane and solvent a, adjusting the pH to 5.2, and then stirring at room temperature for 1.8 h. The percentage of 5,6-epoxyhexyltriethoxysilane and solvent a in the silane hydrolysate was 14.3 g: 31 mL. Solvent a was obtained by mixing ethanol and water in a volume ratio of 1.3:1. The volume fraction of ethanol was 95%. Step H2: Mix carbon nanotubes and acid solution, heat to 83℃, and reflux and stir for 1.1h to obtain product h2; mix product h1, anhydrous ethanol, DMF, and triethylamine, stir for 38min, add product h2, stir at 85℃ for 10.3h, raise the temperature to 105℃, and continue stirring for 2.1h to obtain product h3; the ratio of carbon nanotubes to acid solution is 1.3g:35mL; the acid solution is a mixture of 68% concentrated nitric acid and 98% concentrated sulfuric acid in a volume ratio of 2:2.5; the ratio of product h1, anhydrous ethanol, DMF, triethylamine, and product h2 is 2.3g:30mL:95L:1.1g:3.5g; Step H3: Triphenylphosphine, 5-bromo-1-pentanol, and anhydrous acetonitrile were mixed, nitrogen gas was introduced, and the mixture was heated to 43°C with stirring for 24.3 h to obtain product h4. Product h4, epichlorohydrin, methanol, and DMSO were mixed, and sodium hydroxide aqueous solution was added with stirring. The mixture was heated to 58°C and stirred for 4.8 h to obtain product h5. The molar ratio of triphenylphosphine, 5-bromo-1-pentanol, and anhydrous acetonitrile was 14.3 g: 9.3 g: 65 mL; the molar ratio of product h4, epichlorohydrin, methanol, DMSO, and sodium hydroxide aqueous solution was 24.5 g: 5.3 g: 18 mL: 53 mL: 33 mL; the mass fraction of sodium hydroxide aqueous solution was 23%. Step H4: Mix product h3, acetonitrile, and methanol and ultrasonically disperse for 45 min. Add N,N-dimethylbutylamine and product h5, and reflux and stir at 95℃ for 6.3 h to obtain product h6. Mix product h6, potassium carbonate, DMSO, and acetonitrile and ultrasonically disperse for 1.1 h. Add acryloyl chloride mixture in an ice-water bath. After addition, raise the temperature to 53℃ and stir for 12.3 h to obtain the auxiliary agent. The ratio of product h3, acetonitrile, methanol, N,N-dimethylbutylamine, and product h5 is 7.5 g: 155 mL: 25 mL: 0.8 g: 15.5 g. The ratio of product h6, potassium carbonate, DMSO, acetonitrile, and acryloyl chloride mixture is 25.5 g: 2.3 g: 175 mL: 40 mL: 38 mL. The acryloyl chloride mixture is obtained by mixing acryloyl chloride and DMSO at a ratio of 4.8 g: 18 mL.
[0020] Example 6 An auxiliary agent, the preparation of which includes the following steps: Step H1: Nano-ferric oxide is added to anhydrous ethanol and ultrasonically dispersed for 35 min. Hydrogen peroxide solution is added dropwise, and the mixture is heated to 50°C and stirred for 1.2 h to obtain the pretreated product. The pretreated product is then added to ethanol and ultrasonically dispersed for 30 min. Silane hydrolysis solution is added, and the mixture is stirred at 65°C for 4.5 h to obtain product h1. The ratio of nano-ferric oxide, anhydrous ethanol, and hydrogen peroxide solution is 2 g:45 mL:40 mL; the mass fraction of the hydrogen peroxide solution is 10%. The percentage of pretreated product, ethanol, and silane hydrolysate was 2.5 g: 45 mL: 30 mL. The silane hydrolysate was obtained by mixing and stirring 5,6-epoxyhexyltriethoxysilane and solvent a, adjusting the pH to 5.5, and then stirring at room temperature for 2 hours. The percentage of 5,6-epoxyhexyltriethoxysilane and solvent a in the silane hydrolysate was 14.5 g: 32 mL. Solvent a was obtained by mixing ethanol and water in a volume ratio of 1.5:1. The volume fraction of ethanol was 95%. Step H2: Mix carbon nanotubes and acid solution, heat to 85℃, and reflux and stir for 1.2h to obtain product h2; mix product h1, anhydrous ethanol, DMF, and triethylamine, stir for 40min, add product h2, stir at 90℃ for 10.5h, raise the temperature to 110℃, and continue stirring for 2.2h to obtain product h3; the ratio of carbon nanotubes to acid solution is 1.5g:40mL; the acid solution is a mixture of 68% concentrated nitric acid and 98% concentrated sulfuric acid in a volume ratio of 3:2.8; the ratio of product h1, anhydrous ethanol, DMF, triethylamine, and product h2 is 2.5g:35mL:100mL:1.2g:4g. Step H3: Triphenylphosphine, 5-bromo-1-pentanol, and anhydrous acetonitrile were mixed, nitrogen gas was introduced, and the mixture was heated to 45°C with stirring for 24.5 h to obtain product h4. Product h4, epichlorohydrin, methanol, and DMSO were mixed, and sodium hydroxide aqueous solution was added with stirring. The mixture was heated to 60°C and stirred for 5 h to obtain product h5. The molar ratio of triphenylphosphine, 5-bromo-1-pentanol, and anhydrous acetonitrile was 14.5 g: 9.5 g: 70 mL; the molar ratio of product h4, epichlorohydrin, methanol, DMSO, and sodium hydroxide aqueous solution was 25 g: 5.5 g: 20 mL: 55 mL: 35 mL; the mass fraction of sodium hydroxide aqueous solution was 25%. Step H4: Mix product h3, acetonitrile, and methanol and ultrasonically disperse for 50 min. Add N,N-dimethylbutylamine and product h5, and reflux and stir at 100℃ for 6.5 h to obtain product h6. Mix product h6, potassium carbonate, DMSO, and acetonitrile and ultrasonically disperse for 1.2 h. Add acryloyl chloride mixture in an ice-water bath. After addition, raise the temperature to 55℃ and stir for 12.5 h to obtain the auxiliary agent. The ratio of product h3, acetonitrile, methanol, N,N-dimethylbutylamine, and product h5 is 8 g: 160 mL: 30 mL: 0.9 g: 16 g. The ratio of product h6, potassium carbonate, DMSO, acetonitrile, and acryloyl chloride mixture is 26 g: 2.5 g: 180 mL: 45 mL: 40 mL. The acryloyl chloride mixture is obtained by mixing acryloyl chloride and DMSO at a ratio of 5 g: 20 mL.
[0021] Example 7 like Figure 1 The spiral modified MBBR filler shown comprises the following raw materials in parts by weight: 100 parts HDPE, 7 parts modified hydrotalcite, 4 parts additives, 0.7 parts initiator, 1 part polyvinyl alcohol, 1 part chitosan, 1.5 parts gelatin, 5 parts activated carbon, 0.5 parts zinc stearate, and 0.3 parts EBS dispersant; the initiator is dicumyl peroxide. The spiral-shaped modified MBBR packing is prepared by the following steps: HDPE (supplier: Dongguan Aolei Plastics Co., Ltd., specification 25kg) and the additives obtained in Example 4 were melt-mixed at 175°C. Then, an initiator was added, and the mixture was heated to 185°C and allowed to melt for 13 minutes. The mixture was then cooled to 80°C, and the modified hydrotalcite obtained in Example 1, polyvinyl alcohol (supplier: Zhengzhou Wandao New Material Technology Co., Ltd., specification 25kg), chitosan, gelatin, activated carbon, zinc stearate, and EBS dispersant were added and mixed at 800 rpm for 10 minutes. The mixture was then heated to 190°C and 300 rpm for melt blending, extruded and granulated, and then extruded by screw extrusion. The blank is formed into a cylindrical part at 180℃; then the cylindrical blank is cut with a carbide spiral cutter. After cutting, it is immersed in water at 75℃ for 1.8 hours, then dried at 60℃ for 4 hours, and then treated with plasma to obtain spiral modified MBBR filler. The diameter of the cylindrical blank is 10 mm and the length-to-diameter ratio is 0.8. The helix angle of the carbide spiral cutter is 30°, the cutter width is 2 mm, and the cutter depth is 1.5 mm. During the cutting process of the carbide spiral cutter, the linear speed is 0.5 m / s and the feed is 0.2 mm / r. The plasma treatment conditions are 300 W power and 90 s time.
[0022] Example 8 like Figure 1 The spiral-shaped modified MBBR filler shown comprises the following raw materials in parts by weight: 103 parts HDPE, 8 parts modified hydrotalcite, 5 parts additives, 0.8 parts initiator, 1.5 parts polyvinyl alcohol, 1.5 parts chitosan, 2.2 parts gelatin, 8 parts activated carbon, 0.8 parts zinc stearate, and 0.4 parts EBS dispersant; the initiator is dicumyl peroxide. The spiral-shaped modified MBBR packing is prepared by the following steps: HDPE (supplier: Dongguan Aolei Plastics Co., Ltd., specification 25kg) and the additives obtained in Example 5 were melt-mixed at 178°C. Then, an initiator was added, and the mixture was heated to 188°C and allowed to melt for 15 minutes. The mixture was then cooled to 85°C, and the modified hydrotalcite obtained in Example 2, polyvinyl alcohol (supplier: Zhengzhou Wandao New Material Technology Co., Ltd., specification 25kg), chitosan, gelatin, activated carbon, zinc stearate, and EBS dispersant were added. The mixture was then mixed at 900 rpm for 13 minutes, and then melt-blended at 195°C and 300 rpm. The resulting product was extruded and granulated using a screw extruder. The blank was formed into a cylindrical part at 95℃; then the cylindrical blank was cut with a carbide spiral cutter, and after cutting, it was immersed in water at 78℃ for 1.9h, then dried at 63℃ for 4.3h, and then treated with plasma to obtain spiral modified MBBR filler; the diameter of the cylindrical blank was 15mm and the length-to-diameter ratio was 1.0; the helix angle of the carbide spiral cutter was 45°, the cutter width was 3mm, and the cutter depth was 2.2mm; during the cutting process of the carbide spiral cutter, the linear speed was 1.0m / s and the feed was 0.3mm / r; the plasma treatment conditions were 400W power and 105s time.
[0023] Example 9 like Figure 1 The spiral modified MBBR filler shown comprises the following raw materials in parts by weight: 105 parts HDPE, 9 parts modified hydrotalcite, 6 parts additives, 0.9 parts initiator, 2 parts polyvinyl alcohol, 2 parts chitosan, 3 parts gelatin, 10 parts activated carbon, 1 part zinc stearate, and 0.5 parts EBS dispersant; the initiator is dicumyl peroxide. The spiral-shaped modified MBBR packing is prepared by the following steps: HDPE (supplier: Dongguan Aolei Plastics Co., Ltd., specification 25kg) and the additives obtained in Example 6 were melt-mixed at 180°C. Then, an initiator was added, and the mixture was heated to 190°C and allowed to melt for 17 minutes. The mixture was then cooled to 90°C, and the modified hydrotalcite obtained in Example 3, polyvinyl alcohol (supplier: Zhengzhou Wandao New Material Technology Co., Ltd., specification 25kg), chitosan, gelatin, activated carbon, zinc stearate, and EBS dispersant were added and mixed at 1000 rpm for 15 minutes. The mixture was then melt-blended at 200°C and 400 rpm, extruded and granulated, and then extruded through a screw extruder. The blank was formed into a cylindrical part at 210℃ using a press; then the cylindrical blank was sheared with a carbide spiral cutter, and after shearing, it was immersed in water at 80℃ for 2 hours, then dried at 65℃ for 4.5 hours, and then treated with plasma to obtain spiral modified MBBR filler; the diameter of the cylindrical blank was 25mm and the length-to-diameter ratio was 1.2; the helix angle of the carbide spiral cutter was 60°, the cutter width was 4mm, and the cutter depth was 3mm; during the shearing process of the carbide spiral cutter, the linear speed was 1.5m / s and the feed was 0.5mm / r; the plasma treatment conditions were 500W power and 120s time.
[0024] Comparative Example 1 Compared with Example 9, the 2-methoxy-5-aldehyde pyrimidine used in the preparation process of the modified hydrotalcite was replaced with 5-methoxypyridine-2-aldehyde, and the rest was exactly the same as in Example 9, to obtain the filler.
[0025] Comparative Example 2 Compared with Example 9, the 4-nitroimidazole used in the preparation process of the modified hydrotalcite was replaced with N-methyl-p-nitroaniline, and the rest was exactly the same as in Example 9, to obtain the filler.
[0026] Comparative Example 3 Compared with Example 9, the modified hydrotalcite used was replaced with modified hydrotalcite-1, that is, modified hydrotalcite-1 was obtained by reacting product g9 with zinc-aluminum hydrotalcite in step G5. The rest was exactly the same as in Example 9, and the filler was prepared.
[0027] Comparative Example 4 Compared with Example 9, the triphenylphosphine used in the preparation process of the auxiliary agent was replaced with triethylamine, and the rest was exactly the same as in Example 9, to obtain the filler.
[0028] Comparative Example 5 Compared with Example 9, the carbon nanotubes used in the preparation process of the additives were replaced with halloysite nanotubes, and the rest was exactly the same as in Example 9, to obtain the filler.
[0029] The filler prepared according to the present invention was further tested, and the test results are as follows.
[0030] The packing materials obtained in Examples 7-9 and Comparative Examples 1-5 of this invention were placed in the same fluidized bed reactor and tested under the same conditions. Simulated high-salt domestic sewage (influent COD 300 mg / L, TN 40 mg / L, TP 4 mg / L, 25℃, DO 2-3 mg / L, NaCl 600 mg / L) was used. The packing material addition rate was 40%, and the temperature was 23-27℃. The COD, TN, and TP content of the effluent was collected and measured daily. Once the effluent indicators stabilized, biofilm formation was considered complete. The biofilm formation time was recorded, and the COD, TN, and TP removal rates were calculated. The fillers obtained in Examples 7-9 and Comparative Examples 1-5 of this invention were placed in an ultraviolet aging test chamber for accelerated ultraviolet aging tests. The test conditions were: temperature 70°C, humidity 70%, and ultraviolet intensity 0.68 W / m². 2 The aging time was 500 hours. After aging, the removal rates of COD, TN, and TP were measured according to the above method. The results are recorded in Table 1; Table 1: Test Results According to the data in Table 1, the MBBR packing of the present invention exhibits a faster biofilm formation rate, higher COD, TN, and TP removal rates, and stronger anti-aging properties. Comparing Example 9 with Comparative Example 1, it is evident that replacing the 2-methoxy-5-aldehyde pyrimidine in the modified hydrotalcite preparation process with 5-methoxypyridine-2-aldehyde reduces the COD, TN, and TP removal rates and weakens the anti-aging properties of the MBBR packing after aging. Comparing Example 9 with Comparative Example 2, it is evident that replacing the 4-nitroimidazole in the modified hydrotalcite preparation process with N-methyl-p-nitroaniline reduces the COD, TN, and TP removal rates and weakens the anti-aging properties of the MBBR packing after aging. Comparing Example 9 with Comparative Example 3, it can be seen that replacing the modified hydrotalcite with modified hydrotalcite-1 (obtained from product g9 intercalated zinc-aluminum hydrotalcite) not only reduces the anti-aging properties and weakens the compatibility with the matrix, but also weakens the hydrophilicity of the MBBR filler, reduces the biofilm formation rate, and decreases the removal rates of COD, TN, and TP. Comparing Example 9 with Comparative Example 4, it can be seen that replacing triphenylphosphine in the preparation process with triethylamine reduces the biofilm formation rate and the removal rates of COD, TN, and TP. Comparing Example 9 with Comparative Example 5, it can be seen that replacing carbon nanotubes in the preparation process with halloysite nanotubes reduces the removal rates of COD, TN, and TP.
[0031] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.
Claims
1. A spiral modified MBBR media, characterized in that: The raw materials include the following parts by weight: HDPE 100-105 parts, modified hydrotalcite 7-9 parts, additives 4-6 parts, initiator 0.7-0.9 parts, polyvinyl alcohol 1-2 parts, chitosan 1-2 parts, gelatin 1.5-3 parts, activated carbon 5-10 parts, zinc stearate 0.5-1 part, and EBS dispersant 0.3-0.5 parts; The initiator is dicumyl peroxide; The modified hydrotalcite is prepared by the following steps: Step G1: Add thiophene aldehyde to acetic anhydride, stir, add potassium salt, heat and reflux with stirring to obtain product g1; add product g1 to DMF, stir and add thionyl chloride, heat and reflux with stirring to obtain product g2; mix nitroimidazole and DMSO, stir, and add the mixture of product g2 dropwise in an ice-water bath, heat and stir after the addition is complete to obtain product g3. The thiophene aldehyde is 3-thiophene carboxaldehyde, the nitroimidazole is 4-nitroimidazole, and the potassium salt is anhydrous potassium carbonate; The mixture of product g2 is obtained by mixing product g2 with DMSO; Step G2: Mix product g3, DMAC, and ethanol solution, stir and add sodium dithionite, and stir to obtain product g4; Product g4, epichlorohydrin, and DMF were mixed and stirred. Tetra-n-butylammonium chloride was added, and the mixture was heated and stirred. Then, an alkaline solution was added, and stirring was continued to obtain product g5. The alkaline solution is a potassium hydroxide or sodium hydroxide solution with a mass fraction of 40-45%. Step G3: Add aldehyde pyrimidine to acetic anhydride, stir, add anhydrous potassium carbonate, heat and reflux and stir to obtain product g6; mix product g6, DMAC and triethylamine, stir, add product g5, heat and stir, then heat and stir again to obtain product g7. The aldehyde pyrimidine is 2-methoxy-5-aldehyde pyrimidine; Step G4: Sodium carboxybenzenesulfonate, DMSO, and ethanol are mixed and stirred. Then, thionyl chloride is added, and the mixture is heated under reflux and stirred to obtain product g8. Product g7, ethyl acetate, and DMAC are mixed and stirred. Then, the mixture of product g8 is added to an ice-water bath and heated under reflux and stirred to obtain product g9. Under a protective gas atmosphere, product g9, DMF, and ethanol are mixed, and the mixture is refluxed and stirred. Then, aqueous acetic acid solution and zinc granules are added and refluxed and stirred to obtain product g10. The sodium carboxybenzenesulfonate is sodium 3-carboxybenzenesulfonate; The mixture of product g8 is obtained by mixing product g8 and DMF; Step G5: Add zinc chloride and aluminum chloride hexahydrate to deionized water, stir and adjust the pH, heat and stir, then age, wash and dry to obtain zinc aluminum hydrotalcite; add zinc aluminum hydrotalcite and product g10 to solvent 1, ultrasonically disperse, stir and adjust the pH, heat and stir, wash until neutral and dry to obtain modified hydrotalcite. Solvent 1 is obtained by mixing ethanol and water, with the volume fraction of ethanol being 95%. The preparation of the auxiliary agent includes the following steps: Step H1: Add nano-iron oxide to anhydrous ethanol, disperse by ultrasonication, add hydrogen peroxide solution, heat and stir to obtain the pretreated product; The pretreated product was added to ethanol, ultrasonically dispersed, and then silane hydrolysate was added. The mixture was heated and stirred to obtain product h1. In step H1, the silane hydrolysate is obtained by mixing and stirring silane and solvent a, adjusting the pH to 5-5.5, and then stirring at room temperature for 1.5-2 hours; the silane is 5,6-epoxyhexyltriethoxysilane; solvent a is obtained by mixing ethanol and water, with the volume fraction of ethanol being 95%. Step H2: Mix carbon nanotubes and acid solution, heat and reflux with stirring to obtain product h2; mix product h1, anhydrous ethanol, DMF and triethylamine, stir and then add product h2, heat and stir to obtain product h3. The acid solution is obtained by mixing concentrated nitric acid with a mass fraction of 68% and concentrated sulfuric acid with a mass fraction of 98%. Step H3: Triphenylphosphine, bromoethanol, and anhydrous acetonitrile are mixed, a protective gas is introduced, and the mixture is heated and stirred to obtain product h4; product h4, epichlorohydrin, methanol, and DMSO are mixed, and an aqueous sodium hydroxide solution is added while stirring, and the mixture is heated and stirred to obtain product h5; The bromo-1-pentanol is 5-bromo-1-pentanol; Step H4: Mix product h3, acetonitrile, and methanol and disperse by ultrasonication. Add N,N-dimethylbutylamine and product h5, and heat and reflux to obtain product h6. Mix product h6, potassium carbonate, DMSO, and acetonitrile and disperse by ultrasonication. Add acryloyl chloride mixture in an ice-water bath, and heat and stir after addition to obtain the additive. The acryloyl chloride mixture is obtained by mixing acryloyl chloride and DMSO.
2. A process for the preparation of the spiral modified MBBR media as claimed in claim 1, characterized in that: The process includes the following steps: HDPE and additives are heated and melted together, then an initiator is added, and after the mixture is heated and melted, it is cooled down. Modified hydrotalcite, polyvinyl alcohol, chitosan, gelatin, activated carbon, zinc stearate, and EBS dispersant are added and mixed together, then heated and melted together, extruded and granulated, and then thermoformed into cylindrical blanks by screw extrusion. The cylindrical blanks are then cut with a carbide spiral cutter, soaked in water after cutting, removed and dried, and then treated with plasma to obtain spiral modified MBBR filler.
3. The process for the preparation of helically modified MBBR media as claimed in claim 2 wherein the process comprises the steps of: The diameter of the cylindrical blank is 10-25mm, and the length-to-diameter ratio is 0.8-1.2; the helix angle of the carbide spiral cutter is 30-60°, the cutter width is 2-4mm, and the cutter depth is 1.5-3mm; during the shearing process of the carbide spiral cutter, the linear velocity is 0.5-1.5m / s and the feed is 0.2-0.5mm / r; the plasma treatment conditions are 300-500W power and 90-120s time.
4. Use of the spiral modified MBBR media as claimed in claim 1, wherein: The spiral-shaped modified MBBR packing is used for wastewater treatment.
Citation Information
Patent Citations
Intercalated hydrotalcite anti-ultraviolet aging agent for rubber as well as preparation method and usage method thereof
CN107022115A
Anti-aging polypropylene material based on fiber reinforcement and preparation method thereof
CN112048125A
